Theology and difference : the wound of reason - Lowe, Walter James, 1940- (Indiana series in the philosophy of religion., 1993)
Theology and Difference reconceives the options confronting modern theology and investigates the disputed questions that underlie it. Pressing beyond the ready-made enlightenment offered by the subject-object framework, Walter Lowe uncovers a number of remarkable convergences between the contemporary philosopher Jacques Derrida and the early twentieth-century theologian Karl Barth. --From publisher's description.